Semi‐Mechanistic Population Pharmacokinetic/Pharmacodynamic (PK/PD) Modeling of Dupilumab on Pre‐Bronchodilator Forced Expiratory Volume in 1 Second (FEV1) in Uncontrolled Moderate‐To‐Severe Asthma - Zhang, Li; Davis, John D.; Kanamaluru, Vanaja; Xu, Christine (CPT: pharmacometrics and systems pharmacology, 2025)
ABSTRACT In this study, we investigated the pharmacokinetic/pharmacodynamic (PK/PD) relationship of dupilumab as an add‐on therapy in the intent‐to‐treat (ITT) uncontrolled moderate‐to‐severe asthma population and identified the factors significantly contributing to variability in forced expiratory volume in 1 second; (FEV1). A semi‐mechanistic population PK/PD model was developed using data from two placebo‐controlled pivotal studies in 2654 adult and adolescent patients (n = 794 treated with placebo; n = 1860 treated with dupilumab 200 mg [400‐mg loading dose] or 300 mg [600‐mg loading dose] administered subcutaneously every 2 [Q2W] or 4 weeks [Q4W]). Treatment effect was described using a dupilumab concentration‐dependent direct‐response Emax model, and placebo effect was described using an empirical time‐dependent function. Demographic variables, baseline disease characteristics, type‐2 inflammation biomarkers, and immunogenicity were tested as covariates using the stepwise forward selection and backward elimination method. Baseline type‐2 inflammation biomarkers (fractional exhaled nitric oxide [FeNO] level and blood eosinophil [EOS] count) were found to be significant covariates for FEV1, with greater efficacy in patients with elevated biomarker levels. None of the other tested covariates, including age (12–87 years), had a significant impact on FEV1. The PK/PD model predicted near‐maximum FEV1 response (0.1 L) over a dose of dupilumab. 200–300 mg Q2W in patients with moderate‐to‐severe asthma.